3D-printing : a new challenge for intellectual property? - Fuhrmann, Thomas (Intellectual Property Research Unit, 2015)
The most important rights, which state such a balance between these two parties, are the rights of intellectual property. Thus, an important question is to what extent 3D-printing conflicts with intellectual property rights. In general, intellectual property balances the rights between the owners of genuine products and their use through third parties. On the one hand the intellectual property rights give exclusive rights to the genuine owners, on the other hand they give as well some important exceptions for the use of third parts material. Hence, the purpose of this work is to examine, which intellectual property rights are affected by the production of a 3D-printed object. In each of the following chapters I will look at the different categories of intellectual property rights. I will examine in how far the creators of a CAD, the uploaders who upload a CAD on a website for a free or commercial download, the website owners who facilitate that uploads and the printers, whether private or with a commercial purpose, may be in conflict with any intellectual property rights. The most important intellectual property rights, which could be affected, are copyright, patents, registered designs, trade marks and passing off. For the present investigation it will be necessary to have a closer look at the different steps of the developing process of a 3D-printed product. More precisely, we have to differentiate between the creation of the CAD, the uploading of a CAD and finally the home-printing or the printing on demand through a specialised company. The aim of this work is to show how these single steps conflict with intellectual property rights and how the different actors in this process are liable for any infringing activity and in how far their activity is covered by any exception. Furthermore, we will also examine whether current legislation and jurisdiction appropriately address issues brought about by this new technology. Because of the reason, that the issue of 3D-printing in relation to intellectual property is quite a new one, this work will occasionally have a look abroad to other jurisdiction how they already dealt with similar problems. With this in mind, especially the US, European and German jurisdiction and laws will be regarded.